Evaluation of maternal perception of children's weight and Body Mass Index in Tuscany, Italy (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The prevention of overweight is a high-priority public health task. The perception that parents have of their children’s nutritional status is a well recognized risk factor for obesity in children, so the aim of our study was to evaluate mothers’ perceptions of their children’s nutritional status.Methods: We conducted, in 2016, a cross-sectional study enrolling1710 children (third grade of all primary schools ) in Tuscany, as well as their mothers. Mothers’ information were collected through a self-administered questionnaire, while children (weighed and measured) filled a questionnaire under the supervision of qualified personnel.Results: 1449 children completed the questionnaire. 74.12% of mothers were able to correctly identify children BMI. The non correct classification tends to significantly decrease in presence of a high educational level compared to low educational level. Mothers’ BMI seems to not be associated with misclassification. The non correct classification was significantly associated with mothers’ opinion about their children’s eating habit.Conclusion: Our data confirmed that, in Tuscany, a limited percentage of mothers tend to misclassify the nutritional state of their children, but in order to maintain these encouraging results, further efforts should be done in order to make all mothers able to correctly evaluate their children.Statements:Authors declare no conflict of interest. The study was conducted according to the criteria set by the declaration of Helsinki and each subject signed an informed consent before participating to the study. Approval of the protocol was obtained from the institutional review board of the National Institute of Health, including the use of opt-out consent; that is, parents could refuse participation but the lack of a returned form was taken to imply consent to their child’s participation.